Field research on measurement and use of trypanotolerance criteria to enhance trypanotolerant livestock productivity. 1. ILCA's achievements and future plans - D'Ieteren, G.D.M.; Trail, J.C.M. (International Laboratory for Research on Animal Diseases, 1994)
Presents field research on measurement and use of trypanotolerance criteria to enhance trypanotolerant livestock productivity. Reviews approach and steps taken from the early years to the most recent ongoing or planned experiments carried out by ILCA and its partneres in the African Trypanotolerant Network. Discusses more specific research objectives, they are:- estimate heritabilities of, and genetic correlations between, trypanotolerance criteria and health and production traits and use these to design and test selection programmes for N'Dama cattle. In the field of molecular genetics ILCA has been collaborating with ILRAD in the search for candidate markers. It is expected that the development of genetic maps will facilitate the search for disease resistance markers or genes. The biological information on components of trypanotolerance obtained in the field is vital for evaluating the usefulness of DNA markers of breed type and aspects of trypanotolerance for practical selection programmes and in interpreting the possible impact of marker assisted selection.